2019
DOI: 10.1016/j.apgeog.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the drivers of deforestation and agricultural transformations in the Northwestern uplands of Cambodia

Abstract: At the end of the 1990s, the Northwestern uplands of Cambodia were one of the last forest frontiers of the country. In a region that was the last Khmer Rouge stronghold, the opening of former conflict zones after a peace agreement initiated a vast movement of agricultural colonization. This movement was economically triggered by high market demand for agricultural commodities such as maize and cassava and fueled by a massive flow of spontaneous in-migration of land-poor farmers from lowland regions around the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…The scientific studies linking land changes to agricultural public policies are also weak compared to those dedicated to environmental policies (e.g., Lein, 2012). Based on classifications of high resolution images (e.g., Landsat and SPOT), studies have shown the effect (or the absence of an effect) of agricultural policies on land cover and land use in Syria (Ibrahim et al, 2014), the Peruvian Amazon (Chavez et al, 2014), Cambodia (Kong et al, 2019), or in the Yucatan region in Mexico (Turner, 2010). Using MODIS NDVI time series, Lein (2012) showed how an agricultural tax free ordinance issued in 2006 changed the adoption of multiple cropping practices in China, while in Brazil, Arvor et al (2011) developed satellite-derived indices to describe the agricultural dynamics in Amazonia between 2000 and 2007 in relation to the existing public policies.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific studies linking land changes to agricultural public policies are also weak compared to those dedicated to environmental policies (e.g., Lein, 2012). Based on classifications of high resolution images (e.g., Landsat and SPOT), studies have shown the effect (or the absence of an effect) of agricultural policies on land cover and land use in Syria (Ibrahim et al, 2014), the Peruvian Amazon (Chavez et al, 2014), Cambodia (Kong et al, 2019), or in the Yucatan region in Mexico (Turner, 2010). Using MODIS NDVI time series, Lein (2012) showed how an agricultural tax free ordinance issued in 2006 changed the adoption of multiple cropping practices in China, while in Brazil, Arvor et al (2011) developed satellite-derived indices to describe the agricultural dynamics in Amazonia between 2000 and 2007 in relation to the existing public policies.…”
Section: Introductionmentioning
confidence: 99%
“…increasing accessibility to previously remote areas through roads and other infrastructure, which tend to cause rapid land degradation due to intensive resource extraction (Hall 2011). Rapid land use and land cover changes (with high carbon loss) along the Thai border are explained by the opening of a former conflict zone, as this region was the last Khmer Rouge stronghold (Kong et al 2019). After peace agreements, this area experienced a rapid influx of land-poor farmers from lowland regions of Cambodia.…”
Section: Hotspots Of Carbon Loss Within and Outside Of Economic Land mentioning
confidence: 99%
“…After peace agreements, this area experienced a rapid influx of land-poor farmers from lowland regions of Cambodia. Refugees also came searching for land to establish cash-crop farms for maize and cassava production, triggered by high market demands of these crops at the time (Kong et al 2019). Mahanty (2019) links more recent deforestation trends along the Vietnamese border to both direct and indirect effects of the of ELCs.…”
Section: Hotspots Of Carbon Loss Within and Outside Of Economic Land mentioning
confidence: 99%
See 1 more Smart Citation
“…There is no scarcity of research examining the relationship between patterns of land use and land cover (LULC) and influencing processes (Bürgi et al, 2004;Cassidy et al, 2010;Kong et al, 2019;Plieninger et al, 2015;Seto et al, 2002). However, the complexity of such relationships, including the variability observed at different spatial and temporal scales is often less well understood.…”
Section: Introductionmentioning
confidence: 99%